Wordsworth and the Cultivation of Women. - Page, Judith W. (UC Press voices revived., 2022)
Focusing on the poems of Wordsworth's ""Great Decade,"" feminist critics have tended to see Wordsworth as an exploiter of women and ""feminine"" perspectives. In this original and provocative book, Judith Page examines works from throughout Wordsworth's long career to offer a more nuanced feminist account of the poet's values. She asks questions about Wordsworth and women from the point of view of the women themselves and of eighteenth- and nineteenth-century.